Urban Morphology Aspects on Microclimate in a Hot and Humid Climate - Paramita, Beta; Matzarakis, Andreas (Geographica Pannonica, 2019)
Bandung, the capital of West Java province, Indonesia has experienced rapid urbanization, which has affected the urban environment, including its building density, land use, and the quality of urban living. This specific urban morphology has had a significant effect on the urban microclimate. This study was aimed at describing the urban microclimate of three different overcrowded settlements, i.e., Linggawastu (overcrowded settlement), Gerlong Girang (moderately crowded), and Pasir Impun (leastcrowded). The discussion will detail aspects of the masses and buildings, the distance between buildings, the height of buildings, and the availability of green open spaces to give the perspective of urban morphology toward the microclimate. Fixed weather logger in those three locations were collected over one month, meanwhile the mobile measurements to find the micro-meteorological values of air temperature (Ta), globe temperature (Tg), humidity (RH), and wind speed (v) to define the mean radiant temperature (Tmrt). The liviThe measurements provided evidence of the trend of heat trapped in densely populated settlements shown in the diurnal temperature range from Tamax and Tamin (△Ta) as only 3.2 °C. Meanwhile in Pasirimpun, which is least populated, △Ta = 9.5°C. Linggawastu with BCR > 96% gave the contribution of low Tg=28.3° C, as there is less insolation penetration to the area. Thus, the PET for two densely populated areas, Linggawastu and Gerlong Girang, tends to be neutral to slightly cool. Nevertheless, this study points out the high humidity in the morning and afternoon, as well as the low air velocity, is a strong affecting factor.